Pulmonary pleomorphic carcinoma: A case harboring EGFR mutation treated with EGFR‐TKIs. Issue 6 (19th April 2018) - Masuda, Ken; Tokito, Takaaki; Azuma, Koichi; Yanagida, Eriko; Nakamura, Masayuki; Naito, Yoshiko; Matsuo, Norikazu; Ishii, Hidenobu; Yamada, Kazuhiko; Akiba, Jun; Hoshino, Tomoaki
Abstract : Pulmonary pleomorphic carcinoma (PPC) is a very rare type of primary lung cancer with an aggressive clinical course. Few reports have documented therapeutic options for PPC with EGFR mutations. Herein, we report a case of PPC with EGFR mutation treated with EGFR‐tyrosine kinase inhibitors (TKIs). A 65‐year‐old Japanese woman was diagnosed with stage IV lung adenocarcinoma with L858R point mutation in exon 21. Despite treatment with erlotinib, the patient died after two weeks as a result of rapid disease progression. Postmortem examination indicated that the thoracic tumors consisted primarily of spindle/sarcomatous components, while expression of the mutated EGFR protein was only observed in adenocarcinoma components. We speculate that the tumor was not driven by EGFR mutation. Clinicians should bear in mind the possibility of pleomorphic carcinoma if EGFR‐TKI treatment fails to achieve a clinical response for adenocarcinoma harboring an activating EGFR mutation diagnosed on the basis of small biopsy specimens.